PENGARUH MEDIA BERMAIN DENGAN PERKEMBANGAN ANAK DIUKUR DENGAN DENVER II PADA ANAK USIA TODDLER (1-3 TAHUN) - Wulandari, Setyo Retno; Kartikasari, Galuh (Jurnal Kesehatan Samodra Ilmu (JKSI), 2016)
Background : Children on Toddler age period (1-3 years) have a golden period in their growth. Many parents often only pay attention to how their children become good growth, just seen from the weight and height of children, They didn’t think for the development of their children to be good. Child development can be assessed using the Denver Development Screening Test (Denver II), while the aspects assessed in this development are the development of gross motor, fine motor, language, social and personal. To make child optiamal in their development, they need to get stimulation like the media play stimulation for them. That can stimulate the development of children, such as motion exercises, talking, thinking, independence and socialization. Actually that activity can stimulate the child's development.. Based on the preliminary survey conducted by researchers in Early Education of Kuncup Mekar, Kadipaten Lor Yogyakarta contained a child in suspect category of children development, even though he is also actively participated in the early education of Kuncup Mekar each month. Research methods : The populations in this study are all children on toddler age in Early Education Kuncup Mekar, Kadipaten Lor Yogyakarta some 22 childrens, the sampling technique used is total sampling. The analysis used in this research is the analysis of univariate and bivariate analysis. Univariate analysis is used to describe an overview of child development, while the bivariate analysis is used to determine the effect on the development of children's play media use Pre - Experiment type of study one group pretest- posttest design. All Tests hipotesi in this study , using SPSS for Windows .Results and discussion : based on statistical test using t-test Sig Value Test can know where the figure of 0,000 is smaller than 0.05 . This means their influence on the development of child's play media measured by DENVER II On Child on Toddler Age ( 1-3 years ) .